ANADOLU'NUN SİYASİ TARİHİ ÜZERİNE BİR İNCELEME (XI VE XII. YÜZYILLAR) - TAŞDEMİR, SAMET (Fırat Üniveristesi, 2024)
Bu çalışma, tarih boyunca birçok medeniyete ev sahipliği yapmış Anadolu'nun özellikle de XI. ve XII. yüzyıllarda geçirmiş olduğu istilalar, Anadolu'da meydana gelen savaşlar ve bölge de kurulan devletler hakkında bilgi vermeyi amaçlamıştır. Anadolu Coğrafyası, bulunduğu jeopolitik konum itibarıyla birçok kavmin iştahını kabartmış ve pek fazla savaşa ev sahipliği yapmıştır. Farklı dinlere, farklı kültürlere ve farklı toplumlara da ev sahipliği yapan Anadolu, çok fazla el değiştirmiş ve çok tahribata uğramıştır. Biz bu çalışmamız da Anadolu coğrafyasının siyasi ve sosyal yapısını inceleyerek özellikle XI ve XII. yüzyıllarda meydana gelen siyasi olayları ve bu olayların neden olduğu kültürel hayatı incelemeyi amaçlıyoruz.

This study focuses on Anatolia, which has hosted many civilizations throughout history, especially in the XI. and XII. It aims to give information about the invasions it has undergone in the centuries, the wars that took place in Anatolia and the states established in the region. Anatolian Geography, due to its geopolitical location, whetted the appetite of many tribes and hosted many wars. Anatolia, which also hosts different religions, different cultures and different societies, has changed hands and suffered a lot of destruction. In this study, we examine the political and demographic structure of the Anatolian geography, especially in XI and XII. We aim to examine the political events that took place in the centuries and the cultural life caused by these events.
A study on the political history of Anatolia (XI and XII. centuries)
Keywords: Tarih